2016
DOI: 10.1177/0002716215603319
|View full text |Cite
|
Sign up to set email alerts
|

Realignment and Recidivism

Abstract: California's 2011 Public Safety Realignment created an unprecedented policy experiment by transferring the authority over lower-level felony offenders from the state correctional system to fifty-eight county jail and probation systems. While centered in California, these changes are reflective of an ongoing national conversation about the appropriate level of government at which to focus crime control efforts. In this article, we first situate Realignment in criminological and sociolegal literatures, showing h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 28 publications
1
22
0
1
Order By: Relevance
“…In particular, it is worth determining whether Prop 47's impact on crime (and recidivism for that matter) varies across California's 58 counties, each with different socioeconomic, demographic, and criminal justice profiles. Prior research findings on Realignment reveal that, in fact, its impact on crime and recidivism varies significantly by county (Bird and Grattet, ; Lofstrom and Raphael, 2016) so future research should be aimed at both documenting and attempting to explain this variation. A critical challenge here involves evaluating the effects of policy or practice changes across California counties under conditions of limited data (see Bird and Grattet, ).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it is worth determining whether Prop 47's impact on crime (and recidivism for that matter) varies across California's 58 counties, each with different socioeconomic, demographic, and criminal justice profiles. Prior research findings on Realignment reveal that, in fact, its impact on crime and recidivism varies significantly by county (Bird and Grattet, ; Lofstrom and Raphael, 2016) so future research should be aimed at both documenting and attempting to explain this variation. A critical challenge here involves evaluating the effects of policy or practice changes across California counties under conditions of limited data (see Bird and Grattet, ).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…And Prop 47's reallocation of resources to prevention efforts, they further argue, should significantly improve public safety in the longer term. As evidence in support for some of these claims, proponents turn to scientific evaluations of Realignment, which found that it had no impact on violent crime rates and only a small impact on property crime rates, mainly auto‐theft (Lofstrom and Raphael, 2016; Sundt et al., ; see also Bird and Grattet, , for findings related to Realignment's impact on recidivism).…”
Section: Crime In the Wake Of Prop 47mentioning
confidence: 99%
“…Grattet and Bird (2016) discussed the challenges to interpreting recidivism statistics along these lines. As a further example, Bird, Grattet, and Nguyen () found that because Realignment mandated that revocations be served locally, it appears to have incentivized officials to seek reconvictions in cases that prior to Realignment they may have relied on revocation. Their research also found that prior to Realignment, some parolees who violated their supervision were taken directly to a prison reception center without a formal arrest being entered into the system.…”
Section: Recidivism and California Correctional Reformsmentioning
confidence: 99%
“…Thus, an analysis of changing recidivism patterns must explore evidence of “charge swapping” by examining increases in other kinds of offenses that are similar to drug possession. Prior research also shows that policy changes are often accompanied by changes in population characteristics, and as a result, it is critically important to employ strategies to ensure that apples‐to‐apples comparisons before and after reforms and thus isolate the causal effect of the reform as much as possible (Bird et al., ).…”
Section: Recidivism and California Correctional Reformsmentioning
confidence: 99%
“…In another study tracking parolees during calendar years 2003 and 2004, the authors found that those that were released from prison with a primary offense that fit AB 109 criteria 54 were actually more likely, compared to those convicted of more serious offenses, to acquire new parole violations (Grattet et al, 2009). Finally, a recent recidivism study that created a proxy PRCS control group from a cohort of pre-Realignment prison releases estimates that the average number previous arrests for this group is 18.1 and past convictions is 7.1 (higher than the averages for all prison releases in the same time period) (Bird, Grattet, & Nguyen, 2017).…”
mentioning
confidence: 99%